Application of ozone on rice storage: A mathematical modeling of the ozone spread, effects in the decontamination of filamentous fungi and quality attributes. (May 2020) - Savi, Geovana D.; Gomes, Thauan; Canever, Sílvia B.; Feltrin, Ana C.; Piacentini, Karim C.; Scussel, Rahisa; Oliveira, Daysiane; Machado-de-Ávila, Ricardo A.; Cargnin, Maykon; Angioletto, Elidio
Abstract: Rice is a food crop prone to contamination by toxigenic fungi. Ozone, as a decontamination strategy in the industry, has attractive advantages over traditional food preservation techniques. A contribution to the understanding of ozone as an antifungal agent in rice storage processes is performed in this study. For this, a mathematical model to predict the ozone spread in rice storage in silos was developed. In addition, the effect of ozone application on fungal decontamination and the influence on quality attributes of stored rice were evaluated. This work links the ozone concentration gradient with fungal elimination. A 3D finite element model and experimental measurements determined the ozone concentration throughout the silo. In the inferior portion (where the ozone inlet occurs) showed strong fungi reduction. In this case, an application of 0.393 k g O 3 ⋅ m r i c e − 3 caused 90% fungal elimination. The efficiency of ozone through the silo is different with relation to fungi reduction, which is compatible with the ozone concentration gradient observed in physical model. The ozone treatment was not able to fully reduce the fungi growth in all the portions within the silo, which some fungi strains as Penicillium sp. remained resistant to treatment. With regard to rice quality, starch modifications, lipid peroxidation, protein profile and microstructure alterations did not reflect any significant alteration in the rice treated with ozone. However, during the seed germination, the ozone showed significant inhibition of the coleoptile and seminal root structure in higher exposure time. The use of ozone during the rice storage in silo scale appear as a strong antifungal agent without causing damage to grain quality. However, the efficiency of ozone throughout the silo is different in terms to fungi growth reduction and therefore, it is importance of adopting strategies to homogenize the ozone spread. Highlights: A mathematical model was developed to predict the ozone spread on rice storage in silos. The ozone antifungal effect is compatible with observed in physical model. An application of 0.393 k g O 3 ⋅ m r i c e − 3 caused 90% fungal elimination and some strains remained resistant. The efficiency of ozone through the silo is different in terms to fungi reduction. Alteration in grain quality attributes was not caused after higher ozone exposure.